Retinopathy of prematurity in English neonatal units: a national population-based analysis using NHS operational data. Issue 3 (20th December 2013) - Wong, Hilary S; Santhakumaran, Shalini; Statnikov, Yevgeniy; Gray, Daniel; Watkinson, Michael; Modi, Neena; ,
Abstract : Objectives: To report on retinopathy of prematurity (ROP) screening compliance against a national guideline, factors associated with non-compliance and effect on ROP treatment. Design: National cohort study using operational NHS data from the National Neonatal Research Database (NNRD) for the period 2009–2011. Setting: 161 (94%) neonatal units in England. Population: Infants born below 32 weeks' gestation and/or with a birth weight below 1501 g. Main outcome measures: ROP screening status ('on-time', 'early', 'late', 'unknown') and associated infant and neonatal unit characteristics, ROP treatment. Results: The proportion of infants screened on-time increased over the study period (p<0.001). Of 19 821 eligible infants, 7602 (38.4%) were recorded to have received ROP screening in accordance with the national guideline; 7474 (37.8%) received screening outside the recommended time period; data were missing for 4745 (16.7%) infants. For 16 411 infants in neonatal care during the recommended screening period, late screening was significantly associated with lower gestational age (relative risk ratio (RRR) (95% credible interval) for late versus on-time screening 0.83 (0.80 to 0.86) for each increased week of gestation) and care in a neonatal unit providing less than 500 days of intensive care per annum (2.48 (0.99 to 4.99)). Infants screened late were almost 40% more likely to receive ROP treatment (OR (95% CI) 1.36 (1.05 to 1.76)). Conclusions: Understanding organisational differences between neonatal units may help improve ROP screening. Patient-level electronic NHS clinical data offer opportunity for future rapid, low cost, population-based evaluations but require improved data entry.